Genetic characterization of domestic goat (Capra hircus) using mitochondrial dna - Wan Nor Haslinda, Binti Wan Azman (Universiti Malaysia Sarawak (UNIMAS), 2011)
This study examines the genetic characteristic of domestic goat Capra hircus using sequence analysis of mitochondrial DNA Cytochrome Oxidase I (COI) gene. A total of 20 domestic goat samples from the Handalas Farm, Matang, Sarawak were examined. The sequence data were analyzed using both character (Maximum Parsimony) and distance (Neighbour-joining) methods. Phylogenetic tree produced showed all the goats from the Handalas Farm Matang, Sarawak is clustered into a single clade. The result showed that all the sequences are closely related thus all samples used in this study are possibly originated from a single gene pool of domestic goat population. Overall, analysis from this study showed that the COI gene is limited use in examining the genetic structure of goat population in the Handalas Farm, Matang, Sarawak.